2021
DOI: 10.3390/md19080406
|View full text |Cite
|
Sign up to set email alerts
|

Marine Sulfated Polysaccharides as Promising Antiviral Agents: A Comprehensive Report and Modeling Study Focusing on SARS CoV-2

Abstract: SARS-CoV-2 (severe acute respiratory syndrome coronavirus-2) is a novel coronavirus strain that emerged at the end of 2019, causing millions of deaths so far. Despite enormous efforts being made through various drug discovery campaigns, there is still a desperate need for treatments with high efficacy and selectivity. Recently, marine sulfated polysaccharides (MSPs) have earned significant attention and are widely examined against many viral infections. This article attempted to produce a comprehensive report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 119 publications
0
21
0
Order By: Relevance
“… Step 3 (MDS step): Top-scoring poses resulted from the docking step were subjected to 200 ns MD simulations carried out in duplicates. MDS runs were performed and analyzed by Desmond software [ 14 , 15 , 42 , 43 ]. Step 4 (SMD step): steered molecular dynamics (SMD), was carried out to determine the relative binding affinity of the investigated compounds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… Step 3 (MDS step): Top-scoring poses resulted from the docking step were subjected to 200 ns MD simulations carried out in duplicates. MDS runs were performed and analyzed by Desmond software [ 14 , 15 , 42 , 43 ]. Step 4 (SMD step): steered molecular dynamics (SMD), was carried out to determine the relative binding affinity of the investigated compounds.…”
Section: Methodsmentioning
confidence: 99%
“…Our group has reacted immediately with the pandemic, putting every effort to screen our available extracts, fractions, and pure compounds obtained from plants, endophytes, and microorganisms of marine and terrestrial origin for the discovery of antiviral hits against SARS-CoV-2 or its main protease (M pro ) as a potential target [ 13 , 14 , 15 , 16 , 17 , 18 ]. In the current study, we report the discovery of a previously reported indole diketopiperazine alkaloid neoechinulin A ( 1 ), as a promising SARS-CoV-2 M pro inhibitor through bioguided screening.…”
Section: Introductionmentioning
confidence: 99%
“…However, heparin and derivatives may present severe side effects or complications such as hemorrhage ( 18 , 19 ), thrombocytopenia ( 20 , 21 ), osteoporosis ( 22 , 23 ), hypersensitivity reactions ( 24 ), and hypoaldosteronism ( 25 ). Hence, reports showing potential non-heparin anti-SARS-CoV-2 sulfated glycans, including unique molecules from marine sources, have recently appeared in the literature ( 26 , 27 , 28 , 29 , 30 ). However, these recent reports have studied the actions of the sulfated polysaccharides only against the Wuhan SARS-CoV-2 strain (wild type) and not the mutated variants, including those of more infectious potency.…”
Section: Introductionmentioning
confidence: 99%
“…This is also true for chemically sulfated arabinoxylans, whose antiviral activities vary greatly depending on the degree of sulfation, with highly sulfated polysaccharides being more active [29,46,275]. Incidentally, a modeling study demonstrated that sulfated polysaccharides with a single sulfate or carboxylate group per monosaccharide unit failed to achieve stable binding with either S-protein receptor-binding domain (S-RBD) or ACE2, the human angiotensin-converting enzyme-2 [307] supporting the significance of the extent of sulfation on antiviral efficacy. Moreover, the removal of the sulfate functionality from ulvans [45], fucoidans [73], and chemically sulfated alginates [74,77], glucans [47,275], arabinoxylans [46], and arabinogalactans [44], drastically reduced antiviral activity confirming the importance of sulfate functionality.…”
Section: Relationship Between Structures Of Sulfated Polysaccharide A...mentioning
confidence: 99%